Effect of Shin'iseihaito (Xinyiqingfeitang) on Acute Streptococcus pneumoniae Murine Sinusitis via Macrophage Activation - Minami, Masaaki (Evid Based Complement Alternat Med, 2017)
Streptococcus pneumoniae (S. pneumoniae) causes sinusitis. The general treatment of S. pneumonia sinusitis is by using antibiotics; however, one of their serious problems is the attenuation of their effect. Shin'iseihaito (Xinyiqingfeitang), a formula of Japanese traditional Kampo medicine, has been used for the treatment of sinusitis in Japan. In this study, we investigated the efficacy of Shin'iseihaito against S. pneumoniae-caused sinusitis in mice. Oral administration of Shin'iseihaito extract (SSHT) decreased the nasal colonization of S. pneumoniae in both prophylactic and therapeutic treatments, respectively, and the former was more effective than the latter. Histopathological analysis revealed that the epithelial tissue from S. pneumoniae-infected nose under SSHT treatment recovered the tissue destruction in comparison to infected nose. We also confirmed this result by scanning electron microscopic analysis. Murine peritoneal macrophages from SSHT-treated mice had significant phagocytic activity in comparison to those from untreated group. We also found that tumor necrosis factor-α, interleukin-1β, interleukin-6, and monocyte chemotactic protein-1 levels and the migration of macrophages from S. pneumoniae-infected mice with the treatment with SSHT were increased compared to those from untreated group. Our data suggest that Shin'iseihaito may be useful for the treatment of S. pneumoniae-induced sinusitis.